Extrusion Benchmark 2017: Effect of Die Design on Profile Quality and Distortions of Thin C-Shaped Hollow Profiles. (2019) - Donati, Lorenzo; Segatori, Antonio; Gamberoni, Andrea; Reggiani, Barbara; Tomesani, Luca
Abstract: The Extrusion Benchmark 2017 is focused on the evaluation of different die design strategies for the production of two AA6005A thin C-shaped hollow profiles. The process was monitored in term of press load, profiles speed, profiles exit temperature, die temperatures (with specific focus not only on the die but also on the external die ring) and die deflection. Extruded profiles were analyzed in term of geometrical tolerances, microstructure evolution and profile distortions for both air and water quench; the profiles were also be analyzed for retrieving seam welds positions and charge welds extent.